Halal Risk Management in the Internet Age - Bakar, Ahmad Naqiyuddin; Jaafar, Harlina Suzana; Matulidi, Nornadia (ExcelingTech, 2020)
This paper aims to evaluate the nature of halal risk management by focusing on the advent of online business. Globally, there is a growing trend of halal trading activities from inbound to outbound stages in a virtual marketplace utilising the advancement of online technology. With reference to MS 2400: 2010, an organization must establish a Halalan-Toyyiban Risk Management Plan (HTRMP) following the principles outlined in the standard. This means, beside Halal, the elements for Toyyib should also be considered during risk management, namely the physical, chemical and biological aspects. However, as the Halal items or services originated and processed from all parts of the world, the question of whether these products are genuinely Halal lingers in the minds of the Halal consumers especially among the Muslim communities. Thus, with the complexity of the current world virtual trade scenario, we found the Halal consumers are bound to be sceptical on whether the particular items or products being traded are indeed produced in accordance with the Halal principles and Sharia law or whether it can be construed as Halal when it has to undergo various interfaces in its entire cycle of logistics. The impact of the technology is heavily depending upon the awareness. And the relationship between different stakeholders during the process is another main cause of the risks.